Akame Ga Kill!: A Critique of Power Politics and Authoritarian States in Popular Media - Ramadhan, Erlangga Rizal; Putri, Sylvia Octa; Haryanti, Pitri; Adibowo, Rino (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2026)
This study explores the way the Japanese anime Akame ga Kill! represents the dynamics of power as a critique of authoritarian states in global politics today. By applying qualitative textual content analysis with a focus on cultural and political theory, the work critically examines all 24 episodes of the series. In particular, the paper focuses on the symbolic representation of the state organization, the emerging distribution of power among its elites, and the presence of resistance movements. Despite the existence of constitutional monarchy in the series, the results demonstrate that the actual government is that of personalistic authoritarianism camouflaged in form of empire with a ruling elite exercising real power. The systematic use of coercion and state law as means of oppression is likely to produce major structural inequalities. Discourse in turn confirms the idea that the naturalization of oppression usually leads to radical reactions against the system. Paradoxically, despite being inherently oppressive, authoritarianism seems to possess a fragile nature. In sum, this paper demonstrates that Akame ga Kill! is not only a work of entertainment, but a classic allegory of international property relations and ongoing delegitimization of state rule. As such, the anime emerges as an important tool for the political discussion about systemic injustices and complex issues related to authoritarianism in international context.